TRANSFORMATION OF THE ROLES OF UKRAINIAN UNIVERSITIES TEACHERS IN STUDENT-CENTRED LEARNING AND TEACHING - Bulvinska, Oksana; Chervona, Lesya (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the problem of the readiness of Ukrainian academic staff to transform the role of teacher in student centred learning and teaching. Our research was aimed at studying the readiness of Ukrainian teachers to transform the role of teacher in student-centered learning and teaching. Despite the fact that student-centred approach is confirmed both in normative educational documents and in the theory and practice of European higher education, the teachers of Ukrainian universities are not well-informed about the transformation of the teacher’s role in student-centred learning. And, consequently, the change of the authoritarian role of the teacher to the delicate support of the individual educational search of each student goes hand in hand with some difficulties. The empirical material of the research was collected by the method of questioning of academic staff from Ukrainian universities and students of the Central Institute of Postgraduate Pedagogical Education of the National Academy of Sciences of Ukraine. The results of the study confirmed our hypothesis: Ukrainian university lecturers in the majority of cases are not ready to use flexibly different strategies for interaction with students in order to activate, stimulate and encourage the active educational activities of each student in student-centred learning and teaching.